Open Competitive Exams for Teachers in Oristano between Competence Conflicts and Candidate Evaluation (1866-1913) - Piseri, Federico (Rivista di Storia dell’Educazione, 2022)
The article aims to analyze the recruitment practices for the election of the elementary teachers in Oristano between 1866 and 1913. The research is based on a large documentary investigation that started from f the Municipal and State Archives of Oristano in a first stage, and then continued in the State Archives of Cagliari and Sassari to deepen the careers of the teachers involved. The recruitment sessions held after 1908 are the real focus of the article. These are the subject of numerous appeals that highlight the dynamics of the relationship, often conflictual, between the teachers, the municipality and the institutions ruling the school in a period when, in Italy, is discussed the transition of the primary school administration from the municipalities to the State. What is observed in such a local and decentralized reality, then, finds its confirmation also in the wider national debate.